(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The idea of ​​this work is to find the approximate solutions to the Fredholm and Volterra integral equations of the second kind using the Touchard and Bernstein polynomials. The approximate solutions were compared with the exact solutions to see the accuracy of the method and how effective it is, and to compare the solutions obtained using many terms used among them and in the last they can be compared also with the previously studied works.